2015
DOI: 10.1021/acs.jafc.5b02896
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mutations of the Pectin Methylesterase Gene in Soybean and the Hardness of Cooked Beans

Abstract: Hardness of cooked soybeans [Glycine max (L). Merr.] is an important attribute in food processing. We found one candidate gene, Glyma03g03360, to be associated with the hardness of cotyledons of cooked soybeans, based on a quantitative trait locus and fine-scale mapping analyses using a recombinant inbred line population developed from a cross between two Japanese cultivars, "Natto-shoryu" and "Hyoukei-kuro 3". Analysis of the DNA sequence of Glyma03g03360, a pectin methylesterase gene homologue, revealed thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…A stop codon is inserted in the B and Bʹ genotypes, resulting in amino-acid sequences lacking amino acids that are catalytically important ( Bosch et al 2005 , Jimenez-Lopez et al 2012 ). The cooked bean hardness of soybean carrying the A or Aʹ genotypes was found to be significantly higher than that of soybean carrying the B or Bʹ genotypes ( Toda et al 2015 ), which supports the suggested mechanism of softening tissues by the β-elimination of pectins.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…A stop codon is inserted in the B and Bʹ genotypes, resulting in amino-acid sequences lacking amino acids that are catalytically important ( Bosch et al 2005 , Jimenez-Lopez et al 2012 ). The cooked bean hardness of soybean carrying the A or Aʹ genotypes was found to be significantly higher than that of soybean carrying the B or Bʹ genotypes ( Toda et al 2015 ), which supports the suggested mechanism of softening tissues by the β-elimination of pectins.…”
Section: Introductionsupporting
confidence: 69%
“…Previously, we demonstrated that the hardness of cooked soybeans is affected by genetic factors, and Glyma03g03360 polymorphism, which was recently renamed as Glyma.03g028900 , is associated with the cooked bean hardness ( Hirata et al 2014 , Toda et al 2015 ). Glyma03g03360 encodes a pectin methylesterase (PME) of 490 amino acids in length ( Toda et al 2015 , SoyBase, ). Pectin, which is a major component of primary cell walls and the middle lamella, is mainly constituted of linear chains of 1,4-linked alpha-D-galacturonic acid units.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore possible that different types of selection may have acted on seed hardness-related traits in early domestication and in modern soybean improvement. Concerning the hardness of cooked seeds, a potential causal gene of a major locus, qHbs3-1, was identified as a pectin methylesterase homolog (Toda et al, 2015). Identification of additional genes underlying seed permeability and seed hardness and further evolutionary studies at New Phytologist (2017)…”
Section: Seed Hardnessmentioning
confidence: 99%